PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KEPUASAN KERJA PADA R.S.PKU.MUHAMMADIYAH - Muchroni Subono (MNJ 16 UMY 205, 2016)
This study aims to determine the effect of workload and work stress on job satisfaction of this research for the company as a decision-making for the development of job satisfaction in the company, the era of globalization of job satisfaction to be very note for any company because this is very important to keep our employees in the company , many companies vying to improve the quality of its workload and stress will definitely increase employee by the company because jugak must maintain competent employees' by seeing and improve the quality of their job satisfaction as their rightful wage labor. The sample in this study were taken using the method of data collection is called purposive sampling. The samples used as many as 67 respondents. Data were analyzed using analysis techniques PLS (Partial Least Square) through software SmartPLS. In addition, to test the third hypothesis Sobel test conducted to examine the relationship intervening variables that exist in the hypothesis. The results showed that a third hypothesis to test the effect of indirect variable workloads on job satisfaction through the stress of work carried out by first knowing the results of testing the effect of workload on work stress Keywords: Workload, work stress, job satisfaction, Partial Least Square (PLS) ..